2011
DOI: 10.1016/j.jala.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Site Analytical Evaluation of the BD Viper System with XTR Technology in Nonextracted Mode and Extracted Mode with Seeded Simulated Specimens

Abstract: T he BD ProbeTec CT Q x Amplified DNA Assay and the BD ProbeTec GC Q x Amplified DNA Assay (both BD Diagnostics, Sparks, MD) represent two new assays developed for use with the BD Viper System with XTR Technology (BD Diagnostics). These assays were built on the foundation of the former BD ProbeTec ET assays (BD Diagnostics) and its accompanying instrumentation. The study described below compared the new assay format, Extracted Mode, to the former assay format, Nonextracted Mode, with the primary objective of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…There are few timemotion studies reported in the literature that have evaluated the characteristics of these new platforms, particularly for CT/NG testing. [3][4][5][6][7] Head-to-head evaluations that assess multiple systems using a standardized approach provide critical information to laboratories considering adoption of a new platform. In this study, four automated systems routinely used for the detection of CT/NG were assessed for total run time, hands-on and available walk-away time associated with a run, and ease of instrument set up, operation, and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…There are few timemotion studies reported in the literature that have evaluated the characteristics of these new platforms, particularly for CT/NG testing. [3][4][5][6][7] Head-to-head evaluations that assess multiple systems using a standardized approach provide critical information to laboratories considering adoption of a new platform. In this study, four automated systems routinely used for the detection of CT/NG were assessed for total run time, hands-on and available walk-away time associated with a run, and ease of instrument set up, operation, and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…PCR by itself has revolutionized the science of clinical virology generating numerous novel assays with an obvious impact on the care of immunosuppressed and transplant patients. Cell culture-based assays for C. trachomatis were fully replaced by amplification and for all clinically relevant microorganisms multiple sensitive and specific PCR tests were developed, some of which are now fully automated [6, 30]. Real point-of-care tests for difficult-to-detect organisms including Mycobacterium tuberculosis , are currently available, generating a result within the hour without any complicated sample processing steps [31].…”
Section: Molecular Testingmentioning
confidence: 99%